THE RELATIONSHIP BETWEEN DIGITAL EDUCATION, HEALTH CADRE INVOLVEMENT AND THE TRIPLE ELIMINATION PROGRAMME IN PREVENTING HIGH-RISK PREGNANCIES AT THE BOGOR TENGAH COMMUNITY HEALTH CENTRE IN 2025 - Setyarini, Oktaviani Ike; Pransiska, Cika; Ristanti, Ristanti; Iswandaru, Eryfia Candika; Sari, Ratih Nurma; Hanifa, Fanni; Anggraini, Milka (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The main causes of high maternal mortality rates in Indonesia in 2024, such as haemorrhage, infection, and pre-eclampsia, can actually be detected and prevented during pregnancy through early identification of high-risk pregnancies. Efforts to manage high-risk pregnancies can be carried out through several measures, namely increasing public knowledge, enhancing the role of health cadres, and providing preventive health facilities. Objective: To determine the relationship between Digital Education, the Role of Health Cadres, and the Triple Elimination Programme with the Prevention of High-Risk Pregnancies at the Bogor Tengah Community Health Centre in 2025. Method: This study is an analytical study with a quantitative approach and a cross-sectional design. The study used a survey method, data collection with a questionnaire that had been tested for validity and reliability, and analysis using univariate and bivariate methods. Results: The majority of respondents were in the 26–30 age group (39.1%), had a high school/vocational school education (65.2%), were housewives (78.3%), and had 1–3 pregnancies (78.3%). In the Digital Education Exposure variable, most respondents were in the high category, namely 67 people (97.1%). while the health cadre involvement variable showed that almost all respondents rated the role of cadres as high, namely 68 people (98.6%), and the Triple Elimination Programme variable showed that the majority of respondents were in the high category, namely 67 people (97.1%). Conclusion: There is a relationship between Digital Education, Health Cadre Involvement and the Triple Elimination Programme with the Prevention of High-Risk Pregnancies at the Bogor Tengah Community Health Centre in 2025 (P-value: 0.029; 0.014; 0.029). Suggestion: To be able to